Towards better institutionalisation of domestic solid waste recycling case study : Kuching city - Ng, Chi Boon (Universiti Malaysia Sarawak, (UNIMAS), 2002)
The potential of recycling as an innovative approach to efficient solid waste management is ~o longer a contentious issue. While developed countries have evolved formal strategies in terms of planning, management and organisation for recycling, developing country like Malaysia has yet to formulate and adopt a coordinated approach to recycling. Developed countries have some common features of their recycling programmes, such as a clear defined recycling policy and legislation, as well as organised administrative framework for coordination and implementation of recycling programmes. Recycling in most part of Malaysia especially Kuching City has remained largely informal with scavengers and itinerant waste ..dealers being the major players. DesPite;;1e abundant opportunities to recycle, the ful:l benefits 0: recycling are yet to be exploited. The objectives of the study are to determme the major problems faced by the h seholds of Kuching City in participating in recycling programmes, examine the recycling practices and policies of other countr~ where their recycling programmes have been proved successfully, and design a househ'old recycling framework for Kuching City.